Analysis of Literacy Sociology Approach to Moral Values Contained in the Novel "Limitless Presence" by Hyptin - Linda Nevia Sari; Ali Akbar Jono; Vebby Andra (Jadila: Journal of Development and Innovation in Language and Literature Education, 2023)
The novel "Limitless Presence" by Hyptin illustrates the existence of humans in facing the problems that arise in the life that surrounds them. This research is focused on knowing the moral values contained in the novel "Limitless Presence" by Hyptin. The type of research used is library research, with a qualitative research approach. In this research, the data collection technique used is documentation research (literature study). While the data analysis technique is qualitative data analysis using an iteractive framework. The results of the research are divided into two, namely: (1) The Relationship Between Humans With Themselves such as the value of Honesty, Hard Work, Firm, Firm, Open, Visionary, Independent, Strong, Brave, Responsibility, (2) The Relationship Between Humans with Fellow Humans and Nature such as Happy to Help, Smile, Generous, Cooperative / Able to Work Together, Communicative, Caring (Humans and Nature). There are four roles of moral values, namely: (1) As a Self-Control Tool to Always Do Good, (2) As an Educational Media Moral Learning Tool for Children, (3) As a Unifying Tool for Good Relationships Between Humans, (4) As a Container of Awareness to Preserve Nature. There are six implications such as: (1) strengthening the application of religion in everyday life, (2) making moral values as a means of self-control to always do good in social life, (3) making moral values as a means of communication between people, (4) carrying out activities to instill moral values in the community, (5) obeying every value or norm in society, (6) making moral values as a place of awareness to protect fellow humans and preserve nature.